Protein Hit1, a novel box C/D snoRNP assembly factor, controls cellular concentration of the scaffolding protein Rsa1 by direct interaction. Issue 16 (28th August 2014) - Rothé, Benjamin; Saliou, Jean-Michel; Quinternet, Marc; Back, Régis; Tiotiu, Decebal; Jacquemin, Clémence; Loegler, Christine; Schlotter, Florence; Peña, Vlad; Eckert, Kelvin; Moréra, Solange; Dorsselaer, Alain Van; et al.
Abstract: Biogenesis of eukaryotic box C/D small nucleolar ribonucleoprotein particles (C/D snoRNPs) involves conserved trans -acting factors, which are proposed to facilitate the assembly of the core proteins Snu13p/15.5K, Nop58p/NOP58, Nop56p/NOP56 and Nop1p/Fibrillarin on box C/D small nucleolar RNAs (C/D snoRNAs). In yeast, protein Rsa1 acts as a platform, interacting with both the RNA-binding core protein Snu13 and protein Pih1 of the Hsp82–R2TP chaperone complex. In this work, a proteomic approach coupled with functional and structural studies identifies protein Hit1 as a novel Rsa1p-interacting partner involved in C/D snoRNP assembly. Hit1p contributes to in vivo C/D snoRNA stability and pre-RNA maturation kinetics. It associates with U3 snoRNA precursors and influences its 3′-end processing. Remarkably, Hit1p is required to maintain steady-state levels of Rsa1p. This stabilizing activity is likely to be general across eukaryotic species, as the human protein ZNHIT3(TRIP3) showing sequence homology with Hit1p regulates the abundance of NUFIP1, the Rsa1p functional homolog. The nuclear magnetic resonance solution structure of the Rsa1p317–352 –Hit1p70–164 complex reveals a novel mode of protein–protein association explaining the strong stability of the Rsa1p–Hit1p complex. Our biochemical data show that C/D snoRNAs and the core protein Nop58 can interact with the purified Snu13p–Rsa1p–Hit1p heterotrimer.